Synthesis and dehumidification performance of calcium chloride derived from the waste shells of Anadara granosa - Abdullah, M.Z. (Trans Tech Publications Ltd, 2014)
The waste shell of Anadara granosa or blood cockle is utilized as an alternative source for calcium carbonate (CaCO3) in the synthesis of calcium chloride (CaCl2) as a dehumidifier. In this paper, the synthesis of CaCl2 from the waste shell was investigated at various concentrations of HCl reactant and the shellsâ particle sizes to determine the optimum yield. The synthesized CaCl2 was further tested on its capacity in adsorbing moisture and compared with the commerciallyavailable dehumidifier. It was found that concentration of HCl at 5 M produced the highest yield, while the particle size of 0.5 mm took the shortest period in producing CaCl2 from the waste shells of Anadara granosa. Investigating the performance as dehumidifier in a controlled environment, synthesized CaCl2 showed similar capacity in sorbing moisture as the commercially-available dehumidifier, proving the high potential of the waste shells of Anadara granosa to serve as a green alternative for CaCO3 in producing CaCl2. Â© 2014 Trans Tech Publications, Switzerland.